Is this a valid thing to do, if P and R are both square matrices whose inverse exists?:

P * inverse( I + R*P )

=

inverse( inverse(P) + R )

Printable View

- Jul 1st 2008, 09:48 AMNakanjainverse matrix question
Is this a valid thing to do, if P and R are both square matrices whose inverse exists?:

P * inverse( I + R*P )

=

inverse( inverse(P) + R ) - Jul 1st 2008, 10:13 AMo_O
Sure:

$\displaystyle P(I+RP)^{-1} = \left(P^{-1}\right)^{-1}(I+RP)^{-1} = \underbrace{\left[(I+RP)P^{-1}\right]^{-1}}_{B^{-1}A^{-1} = (AB)^{-1}} $

$\displaystyle = \left[P^{-1} + RPP^{-1}\right]^{-1} = \left[P^{-1} + R\right]^{-1} $ - Jul 1st 2008, 10:25 AMNakanja
Thank you. That $\displaystyle {B^{-1}A^{-1} = (AB)^{-1}}$ part was what I didn't know about.